Acquired factor VIII inhibitor syndrome: A rare cause of hematuria - Muthuvel Seral Kannan; Thallur Ramakrishnan Raj Kumar; Srinivasan Subramanian (Indian Journal of Urology, 2015)
A 50-year-old woman presented with gross hematuria for 1 month. Clinical examinations, laboratory investigations, ultrasound and contrast computed tomography were normal, except anemia. Cystoscopy revealed bloody efflux from the right side. Retrograde pyelogram showed filling defect in the renal pelvis and biopsy was inconclusive. Renal angiogram was normal. She developed ecchymosis on the right thigh and arm with elevated activated partial thromboplastin time. The partial thromboplastin time correction study and Bethesda study confirmed the presence of acquired factor VIII inhibitor (acquired hemophilia). With flexible ureterorenoscopy, the mass in the renal pelvis was removed and its histopathology revealed clotted blood. The patient was subsequently managed with steroids and Factor eight inhibitor bypass activity.